6-Methoxy-2-[(E)-phenyliminomethyl]phenol - Yu, Yu-Ye (International Union of Crystallography, 2011)
The title compound, C(14)H(13)NO(2), was obtained by the condensation reaction of o-vanillin and aniline in ethanol. The molecule adopts the phenol–imine tautomeric form and an E conformation with respect to the azomethine C=N bond. The dihedral angle between the aromatic rings is 30.57 (10)°. In the crystal, molecules are linked by intermolecular C—H⋯O hydrogen bonds into zigzag chains parallel to the b axis.